Prediction of in-hospital mortality in patients with myocardial infarction and type 2 diabetes: the role of cellular indices of systemic inflammation - I. F. Bokovikov; K. V. Protasov (Российский кардиологический журнал, 2024)
Aim. To assess the value of cellular indices of systemic inflammation in the prognosis of in-hospital mortality in patients with ST-segment elevation myocardial infarction (MI) in combination with type 2 diabetes (T2D).Material and methods. The retrospective case-control study included 125 patients with myocardial infarction and T2D, 25 of whom died during the index hospitalization. The cellular composition of the blood and the level of high-sensitivity C-reactive protein (hsCRP) were determined on the first and third days of hospitalization. In the groups of deceased and surviving patients, cellular indices of systemic inflammation were calculated and compared (neutrophil-lymphocyte ratio (NLR), neutrophil-monocyte ratio (NMR), monocyte-lymphocyte ratio (MLR), platelet-lymphocyte ratio (PLR), systemic inflammation index (SII), systemic inflammation response index (SIRI)) and average hsCRP levels). The prognostic role of the studied parameters was assessed using univariate and multivariate logistic regression.Results. Deceased patients, compared with survived ones, had higher Killip class, body mass index, number of stents implanted, higher hsCRP levels, and lower left ventricular ejection fraction. Inhospital mortality was associated with hsCRP (odds ratio of 1,03 with 95% confidence interval of 1,003-1,05, p=0,029), NLR (2,56 [1,73-9,78], p<0,001), NMR (1,16 [1,001-1,35], p=0,04), MLR (23,7 [3,1-182,6], p=0,002), SII (1,001 [1,0-1,001], p=0,028), SIRI (1,29 [1,09-1,52], p=0,003) 48 hours after admission, as well as with the degree of hsCRP change (1,03 [1,003-1,05], p=0,025), NLR (1,58 [1,21-2,06], p=0,001), SII (1,001 [1,0-1,001], p=0,028) during the first three days. Adjusted multivariate regression analysis identified a set of independent predictors with greatest accuracy in assessing the death probability: NLR, SII and SIRI 48 hours after admission, the degree of hsCRP change, body mass index and the num ber of implanted stents.Conclusion. The work demonstrated the significance of cellular indices of systemic inflammation (NLR, SII and SIRI) in assessing the prognosis of in-hospital mortality in patients with MI combined with T2D.